LocBEAT: Authoring tool for the creation of location-based experiences - Castañeda Martinez, Gustavo Leonardo (2017)
With the arrival of Pokemon GO and its positioning as the most successful location-based game, location-based experiences have gained great attention. With the purpose of taking advantage of the growing interest in this type of systems, there is a necessity for designers and developers specialized this type of systems. This necessity can be fulfilled by creating an authoring tool that makes easier the teaching and development of location-based experiences. This authoring tool must be easy to use and user friendly. In order to do this. This research presents the creation, design and evaluation of LocBEAT, a location based experience authoring tool. The creation process involved requirement gathering by doing a literature review of papers related of location based experiences. From these requirements, a low fidelity prototype was designed. This prototype was evaluated using a focus group in order to discover what functions were necessary for the end-user. As a final product of this research, a non-functional high-fidelity prototype of the proposed authoring tool was created using HTML, JavaScript and CSS. An expert usability evaluation was conducted in order to assess its ease of use. The evaluation resulted in an average system usability scale score of 75. Which can be interpreted as a website ‘above good’.